Socioecological factors influencing the risk of developing hypertensive disorders of pregnancy in India: a rapid review - Anumita Alur; Jennifer E. Phipps; Leigh Ann Simmons (BMC, 2024)
Abstract Background The prevalence of hypertensive disorders of pregnancy (HDPs) in India is 11%, which is one of the highest rates globally. Existing research on HDPs in India primarily focuses on biological risk factors, with minimal research on how socioecological factors combine to increase risk of HDPs. We conducted a rapid review using Bronfenbrenner's Ecological Model to understand the social and cultural factors associated with HDPs among Indian pregnant women to identify possible intervention targets that may uniquely improve health in this population. Bronfenbrenner's Ecological Model is a framework that can be used to understand the complex relationship between multiple influences on health. Methods We reviewed studies published between January 2010 and January 2024 using PubMed, Science Direct, and Scopus databases. Search terms included variants of hypertension, pregnancy, and India. Inclusion criteria were: (1) peer-reviewed journal article; (2) published between January 2010 to January 2024; (3) participants consisted of Indian women living in India; (4) studies evaluated socioecological risk factors associated with HDPs. One independent reviewer performed searches, screening, data extraction, and quality assessment. Each included study was then organized within Bronfenbrenner's Ecological Model. Results A total of 921 studies were generated from the initial search, with 157 exclusions due to duplicates. Following screening for inclusion and exclusion criteria at the title/abstract and full text levels, 17 studies remained in the final review. Socioecological risk factors of HDPs were identified at each level, with the most commonly identified influences including: low socioeconomic status (SES), lacking community education and knowledge on HDP management and prevention, and lacking prenatal HDP screening. Conclusion This study determined that the high risk for HDPs in India is influenced by many intertwined socioecological factors. Women in rural and low SES areas need more health education on HDP management and prevention. There also needs to be more adequate prenatal HDP screening, with at least 4 and ideally 8 prenatal visits. Prenatal screenings should be accompanied with culturally appropriate patient education, especially for low SES women who have limited literacy, so that they can effectively make individual and microsystemic lifestyle decisions aimed at either managing or preventing HDPs.